Evaluating the viability of a Tram-Train system. A case study from Salento (Italy). Issue 3 (September 2022) - Ventura, Roberto; Bonera, Michela; Carra, Martina; Barabino, Benedetto; Maternini, Giulio
Highlights: Tram-Train (TT) is a relatively recent transport system, which can integrate features of railway and tramway systems, by using light railways vehicles specifically tailored. Literature on TT system just focused on technical features and description of – few- specific case study. A context analysis is proposed to evaluate the viability of a TT system with respect to the characteristics of the city. A Cost-Benefit Analysis to evaluate the economic sustainability of the project is then tested in the metropolitan area of the Salento (Italy). Abstract: Tram-Train (TT) combines features of railway and tramway systems by mean of tailored light railway vehicles. Although TT systems offer several benefits such as efficiency, effectiveness, and quality, they also incur some issues (e.g., rolling-stock design) that might discourage city administrations from implementation. Further, whilst this system is quite well-known, the related literature is still scarce and relegated to presenting qualitative descriptions of general features, technical issues, and experiments with some TT components. Detailed viability analyses of TT systems implementation in metropolitan areas and evaluation of their economic feasibility have been poorly investigated. This case study addresses previous gaps by a two-tier framework. The first - a context analysis - focuses on a city's features and applies an analytical hierarchy process resulting in a weighted global score to assess the suitability of the specific context for a TT system. If the city achieves a positive evaluation for implementation (according to the score), then the second tier brings a cost-benefit analysis (CBA) into play to assess the project's economic sustainability. Analysis of the Salento (Italy) metropolitan area proved to be a peculiar case study, as it presented uncommon features for TT system employment compared to ideal scenarios from the literature. Nevertheless, by the context analysis, the area resulted viable for such an innovative and interoperable transport system. Indeed, the results highlighted that resource availability and political strategies were far more relevant in the analysis than the spatial and technical features, as well as the need for improving connections. Next, two TT project alternatives were compared through the CBA, and both resulted in economically sustainable, being the net present value positive, the internal rate of return larger than the discount rate and the benefit-cost ratio larger than one. In addition, a sensitivity analysis was applied for the best alternative. It showed that TT investment costs, the marginal cost of accidents, and the demand shifted from the suburban bus and car, respectively, were reported as critical variables. Nonetheless, no switching values were registered that could realistically threaten the assessment of the economic profitability of the TT project. As far as the authors know, these results provide the first empirical evidence of the TT system's viability and its economic feasibility in a mid-sized city based on the development of previous literature recommendations. Hence, this case study may provide a benchmark tool for policymakers, transit experts and the scientific community to assess TT projects.